KEMAMPUAN KOGNITIF MAHASISWA PRODI D III KEBIDANAN PADA MATA KULIAH KELUARGA BERENCANA MELALUI METODE KBK - Nina Primasari Primasari; Fauziah Yulfitria Yulfitria; Dewi Nirmala Sari (Jurnal Ilmu dan Teknologi Kesehatan, 2015)
Implementation of the health education field quick required to respond to the learning process complex and its sustainable hearts produce graduates have the ability work according to science and society accepted. The curriculum of 2002 was developed with reference addressed to the relevant regulations applicable and implementation Of education and health services. Provision of academic education aiming to collect students at the capability of providing health services. Competency based curriculum as concept development curriculum's focus on with ability to implement competency standards specific boarding costs, so the results can be enjoyed learners form of professionalism according to competencies expected. Objective : to know the relation of the competency based curriculum method in cognitive abilities of college students of Family Planning course. Methods : cross sectional with 196 students. The results of ttestshowed that the value of p = 0.000 <0.05, then conclude that the are relations of competency based curriculum method according to the cognitive abilities of the college students. Suggestion : improvement on competency based curriculum implementation, improvement qualityof lecturers in order to support the success of the competency based curriculum and college student more independent with thinking of lecturers as a study partner.